Unusual combination of lesions of the traumatic hand: closed central slip laceration of the extensor and interphalangeal thumb joint's dislocation (a case report) - Boussakri, Hassan; Azarkane, Mohamad; Dahmani, Omar; Elidrissi, Mohamad; Shimi, Mohamed; Elibrahimi, Abdelhalim; Elmrini, Abdelmajid (The Pan African medical journal, 2014)
From the functional standpoint, the hand is one of the most important organs of the body. However, its significance depends largely upon the pincer action of the thumb-index. The management of traumatic lesions of the hand is nowadays' subject of numerous scientific discussions. We present here the case of a patient with a recent laceration of the central slip of the extensor tendon with boutonniere deformity linked to a dislocated interphalangeal thumb of the same hand with a loss of force of the clip thumb and index finger. This combination is a rare lesional of the traumatic hand that has not been previously reported in any orthopedic literature. It was observed after adopting the orthopedic treatment that the range of motion of its joint was at the same level as its healthy side without observing any redislocations during the 6-month follow-up period.